Understanding the commitment efficiency, process and influence of journalism professionalism practces amongst web newspaper journalists in Saudi Arabia / Saleh Zaid Alenizi - Alenizi, Saleh Zaid (2014)
The phenomenon of web journalism in the Kingdom of Saudi Arabia is one of the new practices in Saudi journalism. Despite the newness of this journalistic phenomenon, a number of Saudi web newspapers (more than 250 web newspapers according to a mini-survey conducted to determine the number of Saudi web newspapers) differs in terms of their ideological and professional orientations. There are web newspapers that cover specific regions in Saudi Arabia, web newspapers specializing in a given topic such as sports, children, women, business web newspapers, as well as general web newspapers that cover various topics. With regard to the diversity of the contents of these newspapers, we see it necessary to evaluate and understand the nature of the professional practice in these web newspapers because it is a new experience in Saudi journalism based on measurements of the professional practice developed in previous studies. This study investigates the principles of the professional practice (the journalist’s knowledge about the nature of the professional work and the skills he applied in his work) and the internal and external factors that influence the nature of the practice. The study is divided into five chapters. Chapter One covers an overview about the introduction of web journalism in Saudi Arabia, with the problem statement and research questions. Chapter Two is the literature review. Chapter Three is about the methodology of the study. Chapter Four is about the results and discussion of the study. Finally, Chapter Five covers the conclusion, the scientific and professional contribution of the study in web newspapers, and the recommendations of the study.